Anticancer Potential of Cinnamon Bark Extract (Cinnamomum burmanii) with Cisplatin Combination against P-glycoprotein and Apoptotic Influx Biomarkers - Dina, Sarah; Siregar, M. Fidel Ganis; Jusuf, Nelva K.; Hasibuan, Poppy Anjelisa; Andrijono, Andrijono; Bachtiar, Adang; Lumbanraja, Sarma N.; Nasution, Iqbal Pahlevi (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: To prove the effect of the combination of cinnamon bark extract with cisplatin in reducing efflux and increasing influx in SKOV3 ovarian cancer cell cultures by measuring the expression of p-glycoprotein, CTR1 and the annexim V. Methods: This research is an experimental study using SKOV3 ovarian cancer cells stored in the SCTE IMERI FKUI Laboratory, carried out in the Stem Cells and Tissues Engineering Research Cluster laboratory. The cells were then harvested by adding trypsin-EDTA to the culture as much as 1 mL, and rotated at 2000 rpm for 5 minutes. Then the cells were added with antibodies and dissolved with a stain buffer solution and read on a flow cytometry device. We used ethyl acetate extract from cinnamon bark against the SKOV3 cell line . IC50 of Cinnamon bark extract we got from MTS test. We tested the levels of IC50, 3/4 IC50, 1/2 IC50, and 1/4 IC50 of cinnamon bark extract with a combination of IC50, 3/4 IC50 , 1/2 IC50, and 1/4 IC50 cisplatin against the viability of the SKOV3 cell line with single cisplatin IC50 comparator. We also examined the levels of annexin V as a marker of apoptosis in the SKOV3 cell line to see if the cell cycle arrest induced by cinnamon bark extract could cause apoptosis of the SKOV3 cell line. We assessed the sample distribution using the Shapiro-Wilk test because of the sample size <img src="data:application/pdf;base64,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" alt="equation.pdf">. To assess the comparison of parameters (differences in p Glycoprotein and CTR-1 expression between treatment groups in normally distributed data, the test was used analysis of variance (ANOVA). ANOVA is a comparative test to analyze the difference in the mean (mean) of data from two or more variables in the same population. The Bonferroni test was used to analyze the same or different samples (equal and unequal) in each treatment. Results: From this study, it was found that the combination of IC 50 cinnamon bark extract and IC 50 cisplatin was able to lower p-glycoprotein levels higher with a lower mean value than the other treatment groups with p<0.001. In the test group, the lowest p-glycoprotein expression was found in the combination 1 test group, namely the 1 x IC50 combination. The value of p-glycoprotein expression in the combination group 1 was 1.20%. As for CTR 1, the combination of IC 50 cinnamon bark and IC 50 cisplatin, had the highest CTR1 levels among the three other treatment groups, with p > 0.001. In the test group, the highest CTR1 expression was found in the combination 1 test group, namely the 1 x IC50 combination. The value of CTR1 expression in the combination group 1 was 12%. Conclusion: The combination of cinnamon bark extract with cisplatin was shown to reduce efflux by decreasing p-glycoprotein expression and increasing influx by increasing CTR1 expression in SKOV3 ovarian cancer cell cultures.